Steven Universe : find a way - Kraft, Grace (KaBoom!, a division of Boom Entertainment, Inc., 2019)
Steven Universe and his adventures with the Crystal Gems continue, as he trains with Pearl, Amethyst, and Connie, introduces Peridot to her first video game, and learns how the Crystal Gems built their Beach City home.